More from Louis Baxter on doctors taking MAT. Issue 22 (29th May 2020) - Baxter, Louis E.
Abstract : The question of whether or not doctors and other health care professionals on medication‐assisted treatment (MAT) are safe to practice medicine has been debated for the last few years since the advent of Food and Drug Administration (FDA)–approved MAT for opioid use disorder (OUD). The newly approved medications have been primarily buprenorphine formulations for OUD, naltrexone formulations for OUD and alcohol use disorder (AUD), and, most recently, an alpha 2‐adrenergic medication that specifically targets amelioration of opioid‐withdrawal symptoms from OUD (lofexidine). Quite frankly, the question of safety about medications to treat substance use disorder (SUD) has been asked since the development of methadone for OUD treatment more than 30 years ago.